Fluorinated Nanocarbon Film Electrode Capable of Signal Amplification for Lipopolysaccharide Detection. (10th April 2016) - Oda, Atsumu; Kato, Dai; Yoshioka, Kyoko; Tanaka, Mutsuo; Kamata, Tomoyuki; Todokoro, Masami; Niwa, Osamu
Abstract: We describe a current amplification system that employs a fluorinated nanocarbon (F-nanocarbon) film electrode formed by unbalanced magnetron (UBM) sputtering with a short CF4 plasma treatment. The F-nanocarbon film exhibited the typical electrochemical reaction of a ferrocene-based mediator while strongly suppressing the electrochemical oxidation of Fe 2+ ions. This selectivity provided the current amplification of ferrocene mediators with Fe 2+ ions solely by using the F-nanocarbon film electrode without interference from the direct oxidation current of Fe 2+ ions. The current amplification system was used to realize an electrochemical biosensor with superior performance for detecting lipopolysaccharides. A detection limit of 2 ng mL −1 with good reproducibility (RSD of 4.2%) was achieved thanks to the very low noise made by possible by the ultraflat and hydrophobic surface.